Selected Essential Oils as Natural Ingredients in Cosmetic Emulsions: Development, Stability Testing and Antimicrobial Activity - Shkreli, Rezarta; Terziu, Rihana; Memushaj, Lorena; Dhamo, Klodiola; Malaj, Ledjan (Indian Journal of Pharmaceutical Education and Research, 2023)
Background: Essential oils are currently the subject of intensive scientific study, and their potential as active medicinal compounds or natural preservatives has attracted the attention of the cosmetic and pharmaceutical industries. Objectives: The objectives of the present study were: to develop a cosmetic emulsion based on different concentrations of synthetic preservative and essential oils, applied as natural preservatives; to evaluate and subsequently compare their stability and antimicrobial activity. Materials and Methods: Various samples were prepared using different concentrations of methylparaben, and essential oils as well. The fresh samples were evaluated immediately after preparation related to organoleptic and physicochemical testing. The behavior of the samples related to light tests, accelerated tests, and microbiological stability tests as well were performed for four weeks of storage. Results: During the accelerated stability test, formulations loaded with 2% essential oils were not stable as was noted a variation in the color and liquefaction in the second week of storage at 40°C; their rheological behavior showed a significant decrease in the viscosity, varying from 4890±34.7 to 3720±37.9. For all the samples, the pH levels were within the physiological skin pH range, it varied from 6.01±0.33 to 6.92±0.19. The self-preserving activity of all the cosmetic emulsions was satisfactory. Conclusion: Cosmetic emulsions loaded with essential oils, in the concentration of 1% showed promising stability, physico-chemical characteristics, and self-preserving properties, in different storage conditions. The formulations loaded with essential oils provide a novel alternative for the preservation of “paraben-free” cosmetic products.
Keywords: Cosmetic emulsion; Essential oils; Methylparaben; Formulation; Stability testing; Self-preserving activity